(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
The article describes the structural types of comparisons that are featured in the individual style of A.A. Tarkovskiy. It is determined that by use of full and partial comparisons the poet quite often significantly renews their shape and structure by varying of sign or image. The lack of any element of comparison commonly results in its polysemy, the possibility of multiple interpretations that allow the reader to participate in the process of creating the artistic image and its comprehension. The comparisons used by the poet often involve a micro-plot, at times gaining a symbolic meaning that lays in the implication, while the images of such comparisons gain independent and complete nature.